Effects of Methanol Stem Bark Extract of Annona senegalensis on Kidney Function and Lipid Profile in Diethyl Nitrosamine-Induced Hepatocellular Carcinoma in Rats - Umaru, Isaac John; Abbas, Khalid Yahuza; Omolara, Mosugu Ovayoza; Ekunyi, Agbo Chibuike; Ikira, Usman; Okang, Ogar Fonne; Akem, Ingwu Joseph; Tansaba, Akafa Andes; Frank, Otashu Kenneth; Philip, Shadrach (Darul Yasin Al Sys, 2025)
Hepatocellular carcinoma (HCC) is one of the most prevalent cancers worldwide, with high morbidity and mortality. This study evaluated the anticancer properties of Annona senegalensis stem bark extract in N-diethylnitrosamine (DEN)-induced hepatocellular carcinoma in Wistar rats. Liver carcinogenesis was induced in groups II–VI by intraperitoneal injection of DEN (50 mg/kg body weight in DMSO) once weekly for three weeks. Group II served as the negative control, while group III was the positive control (treated with silymarin, 100 mg/kg b.w.). Groups IV, V, and VI received ethanol extracts of A. senegalensis at 200, 400, and 600 mg/kg b.w., respectively, administered orally for 14 days. Treatment with the extract significantly (p < 0.05) reduced blood urea and creatinine levels, improved electrolyte balance, and enhanced liver histoarchitecture. The extract also favorably modulated lipid metabolism, lowering cholesterol levels from 368.57 ± 1.72 in the negative control to 251.31 ± 1.10 at 400 mg/kg, while increasing HDL levels from 96.21 ± 1.23 to 233.13 ± 0.86 at 600 mg/kg. These results suggest a cardioprotective role via improved lipid profiles. Additionally, kidney function was improved, as reflected by reduced urea (17.30 ± 0.85) and creatinine (2.67 ± 0.23) compared to negative controls (34.53 ± 0.70 and 3.72 ± 0.45, respectively). Overall, the ethanol extract of A. senegalensis demonstrated hepatoprotective, nephroprotective, and lipid-regulating effects, highlighting its potential as a therapeutic agent for mitigating DEN-induced HCC and its associated metabolic complications.